The international tribunal for the law of the sea - Von Brevern, Julie Viktoria (Centre for Law and Society, 2024)
This thesis deals with new developments in the law of the sea which is now widely regulated in the United Nations Convention on the Law of the Sea. Chapter one describes the history of the law of the sea until the Third United Nations Conference on the Law of the Sea of 1982. The main part analyses the newly established International Tribunal for the Law of the Sea. This institution is one of the judicial bodies set up by the Convention on the Law of the Sea to which disputes may be submitted by the States Parties and other appropriate entities for settlement by means of "compulsory procedures entailing binding decisions". It is based in the Free and Hanseatic City of Hamburg and has started its work on the 26 October 1996. The jurisdiction of the International Tribunal for the Law of the Sea is set out in Part V of the Convention as Settlement of Disputes and in Annex VI to the Convention which is called the Statute of the Tribunal. The Tribunal is just one of several alternative institutions which parties to a dispute may choose for settlement of their disputes. Alternative fora are the International Court of Justice, arbitral tribunals constituted in accordance with Annex VII and special arbitral tribunals for certain categories of disputes constituted in accordance with Annex VIII to the Convention. The Convention also provides in Article 280, that the parties to a dispute may settle the dispute by "other peaceful means of their choice". Within the Tribunal the Seabed Dispute Chamber has been established. It has jurisdiction to deal with disputes refering to activities in the area. The Convention declares this area to be "the common heritage of mankind". It vests control of all activities involved with that area in the International Seabed Authority, which acts "on behalf of mankind as a whole" The jurisdiction of the Seabed Dispute Chamber is set out in Part X of the Convention. The principal jurisdiction of the Tribunal and of the Seabed Disputes Chamber, is concerned with disputes about the "interpretation or application" of the provisions of the Convention. The Seabed Dispute Chamber is also in charge of disputes arising in connection with contracts and related arrangements concerning activities for the exploration and exploitation of the resources of the international area. Additionally, the Chamber may give advisory opinions on legal questions within the scope of the activities of those bodies, at the request of the Assembly or Council of the International Seabed Authority. In my opinion one of the main tasks of the Tribunal is the proceeding of prompt release of vessels and crews as provided for in Article 292 of the Convention. This provision of the Convention gives compulsory jurisidiction to the Tribunal. It includes hearing and deciding on cases where it is alleged that it is unreasonably refused to release a detained vessel or its crew upon the posting of a suitable bond or other :financial guarantee required by the applicable law. The tribunal becomes seized of the case only, if the parties to the dispute are not able to resolve the issue among themselves within ten days of the arrest or detention of the vessel or crew. Finally, the expenses of the Tribunal and the Headquarters Agreement, which regulates the relationship between the Tribunal and its hosts, are pictured. Unfortunately the practical ability of the Tribunal's functioning could not be examined as until today no cases have been submitted to the Tribunal.